Aldosterone-to-renin ratio is associated with reduced 24-hour heart rate variability and QTc prolongation in hypertensive patients - Grübler, Martin R.; März, Winfried (Medicine, 2016)
Aldosterone is considered to exert direct effects on the myocardium and the sympathetic nervous system. Both QT time and heart rate (HR) variability (HRV) are considered to be markers of arrhythmic risk and autonomous dysregulation. In this study, we investigated the associations between aldosterone, QT time, and HRV in patients with arterial hypertension. We recruited 477 hypertensive patients (age: 60.2 ± 10.2 years; 52.3% females) with a mean systolic/diastolic 24-hour ambulatory blood pressure monitoring (ABPM) value of 128 ± 12.8/77.1 ± 9.2 mmHg and with a median of 2 (IQR: 1-3) antihypertensive agents. Patients were recruited from the outpatient clinic at the Department of Internal Medicine of the Medical University of Graz, Austria. Blood samples, 24-hour HRV derived from 24-hour blood pressure monitoring (ABPM) and ECG's were obtained. Plasma aldosterone and plasma renin concentrations were measured by means of a radioimmunoassay. Twenty-four-hour urine specimens were collected in parallel with ABPM. Mean QTc was 423.3 ± 42.0 milliseconds for males and 434.7 ± 38.3 milliseconds for females. Mean 24H-HR and 24H-HRV was 71.9 ± 9.8 and 10.0 ± 3.6 bpm, respectively. In linear regression analyses adjusted for age, sex, body mass index, ABPM, and current medication, aldosterone to active renin ratio (AARR) was significantly associated with the QTc interval, a marker for cardiac repolarization abnormalities (mean = 426 ± 42.4 milliseconds; β-coefficient = 0.121; P = 0.03) as well as with the 24-hour heart rate variability a surrogate for autonomic dysfunction (median = 9.67 [IQR = 7.38-12.22 bpm]; β-coefficient = -0.133; P = 0.01). In hypertensive patients, AARR is significantly related to QTc prolongation as well as HRV. Further studies investigating the effects of mineralocorticoid receptor blocker and aldosterone synthase inhibitors on QTc and HRV are warranted.
Gesehen am 28.01.2019